2014
DOI: 10.1002/pits.21757
|View full text |Cite
|
Sign up to set email alerts
|

PROGRAM EVALUATION OF THEPREPaRESCHOOL CRISIS PREVENTION AND INTERVENTION TRAINING CURRICULUM

Abstract: This study details a program evaluation of the PREPaRE School Crisis Prevention and Intervention Training Curriculum (PREPaRE), conducted in the United States and Canada between 2009 and 2011. Significant improvements in crisis prevention and intervention attitudes and knowledge were shown among 875 Crisis Prevention and Preparedness workshop (Workshop 1) participants and 1,422 Crisis Intervention and Recovery workshop (Workshop 2) participants on matched pre‐tests and post‐tests. Results indicated high partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…One estimate suggests that approximately 76,100 psychologists work in schools worldwide with around 32,300 (42%) found in the United States (Jimerson et al, 2009). Psychologists working in schools from the United States, Canada, Germany, and Australia share many common responsibilities, including, for example, data collection and analysis, program evaluation, counseling, consultation with other professionals, crisis preparedness and response, psychoeducational assessment, and the provision of academic, behavioral, and social-emotional supports (Alsoqaih et al, 2017; Bahr et al, 2017; Bell & McKenzie, 2013; Nickerson et al, 2014). These similarities can be seen in the respective countries’ position descriptions for psychologists working in schools.…”
Section: School Psychological Servicesmentioning
confidence: 99%
“…One estimate suggests that approximately 76,100 psychologists work in schools worldwide with around 32,300 (42%) found in the United States (Jimerson et al, 2009). Psychologists working in schools from the United States, Canada, Germany, and Australia share many common responsibilities, including, for example, data collection and analysis, program evaluation, counseling, consultation with other professionals, crisis preparedness and response, psychoeducational assessment, and the provision of academic, behavioral, and social-emotional supports (Alsoqaih et al, 2017; Bahr et al, 2017; Bell & McKenzie, 2013; Nickerson et al, 2014). These similarities can be seen in the respective countries’ position descriptions for psychologists working in schools.…”
Section: School Psychological Servicesmentioning
confidence: 99%
“…The results obtained by Brock and colleagues (2011) and more recent evaluation data indicated significant improvements in crisis prevention and intervention attitudes and knowledge, with high participant satisfaction (Nickerson et al, 2014). PREPaRE was particularly beneficial for participants with fewer hours of prior crisis training (Nickerson et al, 2014).…”
Section: Research Findings and Future Directionsmentioning
confidence: 94%
“…Minimal significant differences between participants trained by a workshop author compared and those trained by a trainer prepared through ToT suggested that the ToT model was successfully implemented. The results obtained by Brock and colleagues (2011) and more recent evaluation data indicated significant improvements in crisis prevention and intervention attitudes and knowledge, with high participant satisfaction (Nickerson et al, 2014). PREPaRE was particularly beneficial for participants with fewer hours of prior crisis training (Nickerson et al, 2014).…”
Section: Research Findings and Future Directionsmentioning
confidence: 94%
“…Studies on the effectiveness of PREPaRE indicate consistent improvements in participants' overall attitudes, knowledge, and skills towards crisis prevention and preparedness (Brock et al, 2011;Nickerson et al, 2014).…”
Section: School Crisis Preparednessmentioning
confidence: 94%